Perancangan Sistem Informasi Pendaftaran Pasien di Klinik Almeta Medika Banjarmasin - Chindy Nadilla Mayora; Husin Husin; Muhammad Zaini; Nurul Noviani (UPPM Politeknik Unggulan Kalimantan, 2024)
Use of information systems is a strategic means for providing registration services that are oriented towards customer satisfaction. Several research results show that there are manual and electronic patient registration systems. The development of Android-based information systems is increasing. Medical records at the Almeta Clinic currently still use a manual system from registration to storage. This research is development research (RnD) with 6 research stages. Carrying out research by creating an outpatient medical resume information system design, researchers created a DFD (Data Flow Diagram), ERD (Entity Relationship Diagram) as well as the appearance and design of a patient registration information system design created with Microsoft Access and Microsoft Visio in accordance with the identification of user needs and requirements. data. The media expert's results showed 80% with the qualification indicators